Proceso de atención de enfermería a un paciente pediátrico con absceso hepático amebiano. - Rosero Paez, Gabriela Carolina (2019)
The present clinical case is of a pediatric patient of eleven years of age who is admitted to the Basic Hospital Arenillas that admitted to the outpatient clinic for presenting abdominal pain of three weeks of evolution, apparent cause of swelling in the abdominal region due to fall, colic-like pain of moderate intensity in the right hypochondrium, accompanied by hyporexia, diarrhea for more than five occasions,hyperthermia, diaphoresis and unquantified weight loss. Laboratory tests are performed with results of Entoeba Histolytics cyst, giardia lambia cyst and abdominal ultrasound is performed, liver abscess located in right lobe of 2.12cm, left lobe of 2.60cm is identified, two are distinguished focal lesions, a round 30 mm in diameter. With a defeinitive diagnosis of amoebis liver abscess. The objective of the clinical case is to develop the process of nursing care for a pediatric patient with amebic liver abscess, the nursing diagnosis is identified with acute pain manifested by loss of appetite Physical infections (abscesses). A nursing care plan is executed, obtaining favorable results that helped to improve the patient's health during his stay in the health home.